Effect of finance on growth through more efficient utilization of technological innovations - Pasi Ikonen (Bank of Finland, 2010)
This paper models the effects of financial development on economic growth through better or more efficient utilization of technological innovations. The model is based on the endogenous growth theory of Aghion and Howitt and its derivatives, especially the growth model of Aghion, Howitt and Mayer-Foulkes, which covers the effect of financial development on convergence. The main contribution of this paper is to model the innovation channel of finance explicitly. The paper focuses particularly on the interaction term between the measure of own innovation and financial development. As countries approach the technological frontier, own innovation becomes more important to sustain a high growth rate. An adequate level of financial development is needed to realize the full potential of own innovation for economic growth. The data covers the period 1960 2007 for anvanced economies, emerging markets and some other countries for which data are available. In estimation of the model, different regression specifications for the data panel are applied. The robustness of the results is also tested in several ways. The results show a significant and positive sign for the interaction term between the measure of own innovation and financial development in the most important configurations. This suggests that the innovation channel of finance is likely to have a positive role to play in economic growth.
URN:NBN:fi:bof-20140807245
Keywords: 330